Game Media as the Fastest Brain Stimulus to Increase Children's Learning Capability - Erlina Sukmawati; Rahmat Mulyono (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2023)
With the development of technology, education is required to be more advanced and modern to be able to keep pace with rapid technological developments. To be able to advance teacher education, they must begin to be open with more modern learning media, one of the learning media that needs to be developed is interactive multimedia based. The problem now is that teachers are not yet open to interactive multimedia-based learning media. The purpose of this study was to understand how simulation and game-based learning media affect students' learning comprehension in